The Effect of Swimming Training on Bone Tissue in Humans - Ragan, Dagmara; Różańska-Smuszkiewicz, Gabriela; Smuszkiewicz-Różański, Paweł; Kmiotek, Weronika; Oronowicz, Radosław; Staszczak, Paweł; Jaworska, Barbara; Długosz, Joanna; Bara, Maciej; Miłkowski, Paweł (Quality in Sport, 2024)
Introduction and purpose: The skeletal system performs many important functions in the human body. It primarily bears the heavy loads associated with movement, protects internal organs, and participates in the regulation of mineral homeostasis. Through continuous processes of bone remodeling and modeling, optimal levels of calcium and phosphorus in the serum are achieved. The balanced removal of old bone tissue by osteoclasts and the formation of new bone by osteoblasts maintain the mechanical properties necessary for the proper functioning of the musculoskeletal system. Bone modeling has been shown to be activated in response to mechanical loading from physical activity. Conversely, the absence of significant loading (as in space travel, i.e., microgravity conditions) leads to increased bone resorption. Osteocytes, as the most numerous group of cells in the skeletal system, are mechanosensitive and are thought to respond to stimuli such as fluid flow, mechanical deformations, and hydrostatic pressure. In response, they regulate the work of osteoclasts and osteoblasts, translating into the regulation of processes occurring in the bone matrix.[1] It is suspected that the type, intensity, and nature of physical exercises can significantly influence these processes. The aim of this work is to gather information on the impact of swimming training (an example of physical exercise in conditions of partial gravity reduction) on the human skeletal system.